(untitled) (Educational Dimension, 2022)
The paper examines the results of a multi-year study to develop an internal certification system for blended and e-learning educational resources in higher education. The authors outline the requirements for internal certification system modeling as well as the characteristics of recent developments in the process of internal certification of educational resources, as permitted by university rules, which is related to the COVID-19 standards. The current model of the internal certification system for educational materials is described in this article, which is based on the approval of the pilot model of e-learning courses (hence — ELC) certification. Three mandatory expertise are the key components of the internal certification method (professional, resource and technical). The methodological commission decides on the quality of the ENC’s educational resources and certification based on the findings. The benefits of using the current system of internal certification of ELC implementation are numerous, including the creation of high-quality educational resources, expanding access to educational content to various categories of participants in the educational process, ensuring individualization of the educational process based on the needs, characteristics, and capabilities of learners, and improving the quality of the educational process.